Analisis Potensi Bahaya di Area Produksi Kelapa Sawit Menggunakan Metode HIRARC di PT. Beurata Subur Persada - Gaustama Putra; Ori Saputra (Jurnal Serambi Engineering, 2022)
In palm oil companies in carrying out the production process, there are still potential hazards in the work area such as at the sterilizer station, thresser station, press station, clarification station and other stations. The method used in solving these problems is the HIRARC method, which aims to reduce the increased risk and create a good work environment. Based on the risk assessment that has been carried out by the author, there are four risk level categories, namely extreme risk, moderate risk, high risk and low risk. At an extreme risk, one of which is broken bones, which can take lives. At moderate risk, one of them is hitting the head on the floor. While at high risk, namely fractures, and sprains. Lastly, the low risk is one of sprains. Risk assessment is given a level in each risk category so that the most dangerous risk is obtained, namely the sterilizer gets level 15, thresser gets level 6, pressing gets level 8, while clarification gets the lowest level, namely 3. Risk control is carried out by providing risk mitigation such as wear PPE, apply SOPs, clean the work area.